Leading your church through conflict and reconciliation: 30 strategies to transform your ministry - Shelley, Marshall; (1953-...) (U.S.A., 1997)
This first volume in the Library of Leadership Development helps pastors and lay leaders understand, prevent, and redeem conflict. Its authors who have survived and thrived in church conflict tell their stories and explain the principles that help them lead through the storms of congregational life.
Keywords: Religious controversies